PENGARUH KEPEMIMPINAN KEPALA MADRASAH DAN KESEJAHTERAAN GURU TERHADAP KINERJA GURU DI MADRASAH ALIYAH NEGERI SE KOTA PAYAKUMBUH - Nadir; Hamdi Abdul Karim (Prodi PAI Sekolah Tinggi Agama Islam Serdang Lubuk Pakam, 2026)
Teacher performance is a key determinant of educational quality; however, variations in the implementation of teachers' professional duties remain evident in State Madrasah Aliyah schools across Payakumbuh City. This study aimed to examine the effects of madrasah principals' leadership and teacher well-being on teacher performance, both individually and simultaneously. A quantitative associative research design was employed involving 105 teachers. Data were collected using validated and reliable questionnaires and analyzed through descriptive statistics, multiple linear regression, t-tests, F-tests, and the coefficient of determination. The findings revealed that principals' leadership had a positive and significant effect on teacher performance (t = 3.539; p = 0.008), while teacher well-being also showed a positive and significant effect (t = 2.465; p = 0.015). Simultaneously, both variables significantly influenced teacher performance (F = 5.369; p = 0.006), explaining 57.9% of the variance in teacher performance. The study concludes that strengthening effective madrasah leadership and improving teacher well-being are essential strategies for enhancing teacher performance and supporting the improvement of educational quality in State Madrasah Aliyah schools.